Redescription of Callianassa jousseaumei Nobili, 1904, a junior subjective synonym of Callianassa indica de Man, 1905 with description of a new species of Neocallichirus (Decapoda: Axiidea: Callianassidae) - Dworschak, Peter C. (Zootaxa, 2011)
Investigation of newly collected material from the Philippines during the Panglao Marine Biodiversity Project 2004, together with re-examination of the type material of Callianassa jousseaumei Nobili, 1904 and numerous specimens identified as Neocallichirus indicus (de Man, 1905), revealed that the latter is identical with the former and has to be considered a junior synonym of Callianassa jousseaumei. A redescription of this species is presented together with notes on its morphological variability and its ecology. A new species of Neocallichirus, N. vaugelasi, is described for specimens from Aqaba, previously attributed erroneously to C. (or N.) jousseaumei, and N. natalensis Barnard, 1947 is removed from the synonymy of the latter. This is the first record of this species for the Philippines and Thailand.